ANALYSIS OF ID, EGO AND SUPEREGO OF THE MAIN CHARACTER IN THE MOVIE SCRIPT CRUELLA BY TONY MCNAMARA AND DANA FOX - Khofifa Ramadhani; Tini Mogea; Merlin Maukar (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this study is to find out how the id, ego and superego of the main character in the movie script Cruella by Tony McNamara and Dana Fox. In this research, the writer used qualitative research and descriptive method, a research method that used non-numerical data to explain a phenomenon accurately. In analyzing this research, the writer used psychological approach, to be exact psychoanalysis theory of id, ego and superego by Sigmund Freud. The writer analyzed the data found in the movie, script, books, journals, articles and websites by several watches of the movie and taking notes on some important parts of the movie script, then applied the theory of psychoanalysis. Based on the results of this study, it was found that the id of Estella, the main character of the movie Cruella is portrayed through her eccentric and quite barbaric thoughts of revenge. The ego is portrayed through how she somehow managed her revenge thoughts into a more realistic ways. And the superego is portrayed through her guilty thought and realization of her true self. It can be concluded that Estella, who also has an alter-ego as Cruella has id as her leading thought, ego that quite often leading her psyche and superego that is the least dominant thought of Estella.